Up in Smoke? The Impact of Smog on Risk Perception and Satisfaction of International Tourists in Beijing. (11th June 2015) - Li, Jing; Pearce, Philip L.; Morrison, Alastair M.; Wu, Bihu
Abstract: This research explored the perceptions of on‐site international tourists towards the smog in Beijing. A scale measuring the degree of tourists' concern about smog conditions was developed. The links among smog concern, risk perception, trip satisfaction and destination loyalty were tested with a structural equation model. Direct relationships were found for the hypothesized effects of smog concern on risk perception and satisfaction. Further, the influence of risk perception on reducing satisfaction as well as the role of satisfaction in forming revisit intention (loyalty) was identified. The broad concerns of this study are applicable across all key Chinese tourism cities visited by international tourists. Copyright © 2015 John Wiley & Sons, Ltd.